Features of marketing in international pharmaceutical market in the context of digital transformation - Marina Korzh; Tatiana Zholudenko (Economic Forum, 2025)
The pharmaceutical market performs a key function of providing the population with medicines, where marketing is the driving force behind meeting the needs for quality healthcare and requires innovative approaches. The research relevance is determined by technological innovations, alongside the severe epidemiological situation in the world and the war in Ukraine, which have changed the requirements for the marketing complex in the pharmaceutical and healthcare markets. The study aimed to deepen the theoretical provisions and develop scientific and practical recommendations for the implementation of marketing innovations in the international pharmaceutical market to increase efficiency and improve and accelerate public access to innovative medicines. The methodological basis was comparative and quantitative methods, tabular analysis and synthesis. The study defined the role of marketing methods and management mechanisms in the international pharmaceutical market. The study analysed the challenges faced by international pharmaceutical market participants related to globalisation and identified the key aspects of international marketing that affect the success of pharmaceutical market management. The study discussed the need to adapt marketing strategies to different cultures and economic conditions inherent in different countries. The study analysed effective methods of promotion in international pharmaceutical markets and examined important aspects of branding and communication to ensure the success of management in the pharmaceutical sector. The study examined modern trends in international marketing in the pharmaceutical sector and identified strategies for adapting to changes in the global economic environment. The role of effective marketing management in creating competitive advantages in international markets was defined, prioritising improvement of the quality of customer service. The study proposed a structural and logical model for the formation of a marketing strategy for the development of business entities in the pharmaceutical market in the global economic space, emphasising their development in the international economic space. The challenges faced by pharmaceutical companies were studied, and the key aspects of international marketing aimed at effective positioning in the global market were identified. The practical significance of the study is determined by the development of a structural and logical model for the formation of a marketing strategy for business entities in the pharmaceutical market, which will contribute to their successful positioning in international markets and increase the efficiency of public access to innovative medicines
Keywords: 330; digital technologies; innovative approaches; competitiveness; communication tools; promotionstrategy; customer focus; adaptation of business models